Fostering organizational commitment: The impact of meaningful work and work engagement among millennial employee - Bayani, Thalia Zati; Matulessy, Andik; Rini, Amanda Pasca (University of Muhammadiyah Malang, 2026)
Millennials tend to have lower organizational commitment than previous generations, which often leads them to change jobs more frequently. Both meaningful work and work engagement have been identified as predictors of organizational commitment. This suggests that organizations can improve employee retention and commitment by enhancing the meaningfulness of work and increasing work engagement. This study involved 118 millennial employees as participants. The instruments employed were the Organizational Commitment Scale, the Meaningful Work Scale, and the Utrecht Work Engagement Scale. The data were analyzed using multiple linear regression. The findings demonstrate a significant positive relationship in which meaningful work and work engagement collectively correlate with organizational commitment. The results also indicate that work engagement contributed 34.5% to organizational commitment, which is higher than the 29.3% contribution of meaningful work. This suggests that although both factors are important, work engagement plays a slightly more substantial role in strengthening organizational commitment. Overall, enhancing the meaningfulness of employees’ roles and fostering higher work engagement may increase organizational commitment.